Pelatihan Penggunaan Sistem Penerimaan Mahasiswa Baru Untuk Mendukung Kelengkapan dan Pelaporan Data PD DIKTI di STIKES Karya Husada Kediri - Achmad Zakki Falani; Made Kamisutara; I Putu Artaya; Eman Setiawan1 (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
The New Student Admission System is an early stage system of academic process in university environment before it progress become the Academic Information System, the Financial Information System, etc. So far, the New Student Admission System is only desaigned for recruiting prospective new students. Based on Undang-undang No. 12 Tahun 2012 about Pendidikan Tinggi and Pemenristekdikti No. 61 tahun 2016 about Pangkalan Data Pendidikan Tinggi they instruct that university have to gives data report into PDDIKTI in period report consistenty.  Based on that rules and development of data reporting process into PDDIKTI, so format of data reporting is also more comprehensive. With utilization and development of  hhe New Student Admission System has been running well in STIKES Karya Husada Kediri, we expect process completion data starting from student biodata can be completed properly. So that all student profile data, especially data regarding PD DIKTI reporting needs, can be completed at the start of the academic process. By carrying out training and mentoring activities on the use of the New Student Admission System, it has been designed to meet the data reporting needs of PD DIKTI in STIKES Karya Husada Kediri. Tthen it is proven that the master data for student biodata in the new intake period is well-completed so that the data can be synchronized accurately and quickly into the PD DIKTI system.